Single and combined effects of beetroot juice and caffeine supplementation on cycling time trial performance - Lane, S. C.; Hawley, J. A.; Desbrow, B.; Jones, A. M.; Blackwell, J. R.; Ross, M. L.; Zemski, A. J.; Burke, L. M. (Applied Physiology, Nutrition, and Metabolism, 2014)
Both caffeine and beetroot juice have ergogenic effects on endurance cycling performance. We investigated whether there is an additive effect of these supplements on the performance of a cycling time trial (TT) simulating the 2012 London Olympic Games course. Twelve male and 12 female competitive cyclists each completed 4 experimental trials in a double-blind Latin square design. Trials were undertaken with a caffeinated gum (CAFF) (3 mg/kg body mass (BM), 40 min prior to the TT), concentrated beetroot juice supplementation (BJ) (8.4 mmol of nitrate (NO3-), 2 h prior to the TT), caffeine plus beetroot juice (CAFF+BJ), or a control (CONT). Subjects completed the TT (females: 29.35 km; males: 43.83 km) on a laboratory cycle ergometer under conditions of best practice nutrition: following a carbohydrate-rich pre-event meal, with the ingestion of a carbohydrate-electrolyte drink and regular oral carbohydrate contact during the TT. Compared with CONT, power output was significantly enhanced after CAFF+BJ and CAFF (3.0% and 3.9%, respectively, p < 0.01). There was no effect of BJ supplementation when used alone (-0.4%, p = 0.6 compared with CONT) or when combined with caffeine (-0.9%, p = 0.4 compared with CAFF). We conclude that caffeine (3 mg/kg BM) administered in the form of a caffeinated gum increased cycling TT performance lasting ~50-60 min by ~3%-4% in both males and females. Beetroot juice supplementation was not ergogenic under the conditions of this study